Exposure to nature through an urban natural monument - Isabel María Muñoz-García; Jorge Alcántara-Manzanares; Jerónimo Torres-Porras (International Journal of Evaluation and Research in Education (IJERE), 2026)
Society is experiencing a decrease in opportunities to connect with nature, a problem that is particularly acute during childhood. Numerous studies indicate that increasing the frequency of participation in nature-related activities in urban environments, through elements such as interpretive trails and sensory trails, improves important variables such as connection with nature (NC) and biodiversity awareness. Therefore, the objective of this study is to determine whether it is possible to foster NC and improve biodiversity awareness in children through a sensory trail in a natural urban environment. This study is part of a project carried out by an educational association that operates in three schools in the city in collaboration with the University of Córdoba, Spain. Therefore, the student population was determined by the association itself, with a total of 111 students aged 10 to 12 (48% female, 52% male). The study consisted of pre-post analyses, and the instruments used were the Cheng and Monroe NC scale and questions to determine children’s knowledge of environmental biodiversity. Data analysis included descriptive statistics to determine correctly identified biodiversity, correlation analysis between variables, and nonparametric tests to determine significant differences. The results reveal a relationship, before completing the route, between NC and nature awareness, and that the intervention had a positive impact on all variables. It is concluded that sensory routes in urban green spaces are an excellent educational resource for fostering NC in children, and their knowledge about biodiversity.